Financiamento e acesso a medicamentos no âmbito da assistência farmacêutica básica no município de Aracaju entre os anos de 2008 a 2012 - Assumpção, Sandro Martins de (2014)
The Pharmaceutical Services are an integral part of the health system and it has in the drug a essential ingredient in the actions in the promotion, protection and recovery of health. Increased access of population to the health system have required changes in the distribution and financing of drugs in order to increase coverage and minimize costs. The present study aimed to evaluate the relationship between the Brazilian governmental financing and assurance the population's access to Drugs, Essential of the Component of Primary Pharmaceutical Care in the city of Aracaju. This is an observational descriptive study of an exploratory nature, the case study type, evaluating the period between the years 2008 and 2012. Work begins rescuing briefly the history of Pharmaceutical Services in the Brazilian Health System and its funding mechanisms in the process of decentralization of health. Proceeds to the analysis of semi -structured interviews conducted by the Pharmaceutical Care`s Municipal Manager, Management Annual Reports of the municipality , reports prepared by Municipal Pharmaceutical Assistance Management and of the deposits made to the account of the Fund allocated to the Municipal Health Component Basic pharmaceutical services and discusses the results. After evaluating the results, it was found that, for the study period, there was sufficient resources to serve all municipal demand for medication of this component, however, it could be seen that there was discontinuity in the supply and consequently, access to these drugs. It is therefore concluded that there was no relationship between sufficiency and ensuring access to Drugs,Essential in the city of Aracaju during the survey period.